Comparative analysis of UWB balance Antipodal Vivaldi Antenna for array configuration - Shaikh, Faraz Ahmed; Khan, Sheroz; Alam, A. H. M. Zahirul; Baillargeat, Dominique; Habaebi, Mohamed Hadi; Yaacob, Mashkuri; Shah, Jawad Ali; Shahid, Zeeshan (IEEE, 2018)
In this paper, an Ultra-wideband Balance Antipodal Vivaldi Antenna in planar and h-plane array configuration is presented. The comparison of four elements of BAVA array in both planes has been observed. Each element of an antenna printed on the glass-reinforced epoxy laminate material (FR4) with a thickness of 1.5mm and relative permittivity of 4.3. The dimension of every single element is 60.75mm x 66mm approximately. The array elements of both planes almost cover the whole UWB frequency range with the reflection coefficient of -10dB. Based on the simulation results, the array elements in planar configuration showing good reflection and works well at 3.2GHz frequency while the configuration in h-plane the array elements works well at 7GHz of frequency. In planar configuration, the operating frequency of antenna elements is shifting as a result of the distance between inter elements which intensification in wavelength. The array elements in h-plane produce more gain up to 10.2 dB with good radiation patterns as compared to the planar plane. The antenna design and optimization development are verified using CST simulation software.